A Study on Swelling Behavior of Poly(p-chloro styrene) Networks in Some Aromatic Hydrocarbons and Linear Poly(p-chloro styrene) Solutions - Celik, Onur; Sakar, Dolunay; Cakar, Fatih; Cankurtaran, Ozlem; Karaman, Ferdane (WILEY, 2009)
Crosslinked networks (NPPCS) and linear polymers (LPPCS) of poly (p-chloro styrene) were synthesized by free-radical polymerization of p-chloro styrene. NPPCS networks were swollen in four different molecular weights of LPPCS solutions in toluene at three different concentrations. The equilibrium swelling results were evaluated by means of Flory-Rehner theory to obtain network-linear polymer interaction parameter, chi'(23) between NPPCS and LPPCS. It was concluded that the parameter chi'(23) decreased with molecular weight but increased with concentration of LPPCS in outer solution. The solvent independent interaction parameter between NPPCS and PPCS was estimated as 0.7 by extrapolation of the Values of chi'(23) to zero value of the fraction ratio of solvent to linear polymer, nu(1)nu(3) inside the network. As well as, the binary interaction parameters, chi(12) of NPPCS with benzene, ethyl benzene, n-propyl benzene and isopropyl benzene were obtained by means of Flory-Rehner theory at temperatures between 25 and 55 degrees C. (c) 2008 Wiley Periodicals, Inc. J Appl Polym Sci 111: 1328-1334, 2009
Keywords: poly(p-chloro styrene); network; swelling behavior; polymer-solvent interaction parameter; polymer-polymer interaction parameter; POLYMER NETWORKS; POLYACRYLAMIDE-GELS; DIVINYLBENZENE; PARAMETERS; SOLVENT; SYSTEMS; Polymer Science